Good Governing Poverty Alleviation Through the PKH Policy - Independent Women's Groups in Poverty Reduction in Batu City (Study at Batu City Social Service) - Maulana, Indah Dwi; Jainuri, Jainuri; Hardini, Hevi Kurnia (Government Studies of Muhammadiyah Malang University/AIPPTM, 2019)
Good Governing Poverty Alleviation is a poverty reduction program by implementing a model of Good Governance in this context in the Family Hope Program - Independent Women's Group involving actors in the state, society and private sector. Handling the poverty problem of the Batu City Government in accordance with the Good Governance model through a partnership pattern established with the private sector, KPM and Batu City Social Service is expected to be able to create independent women's groups that are able to try to develop their creativity to rise from poverty for themselves and their families . This research uses descriptive qualitative method with data collection techniques such as, observation, interviews and documentation and other data that supports this study both primary and secondary. Based on the results of the study of